Portais de periódicos científicos nas universidades federais do estado de Minas Gerais: estrutura, gestão e serviços prestados - Jorge Santa Anna (2018)
Scientific journals have provided many contributions for the development of science, especially for facilitating the exchange of information regarding the research findings. The benefits achieved through the use of this scientific communication medium have led to research studies that use different approaches and have the objective of proposing improvements, especially in view of the increase in the number of these publications, which have migrated to the electronic format, being organized in digital environments: portals of scientific journals. In this context, this research aims to identify the portals of scientific journals in the federal universities of the State of Minas Gerais, describing their characteristics related to content, information architecture, management and services provided. The following procedures were carried out: identification of the federal universities in the State of Minas Gerais; verification of the existence of portals of scientific journals linked to these institutions; and description of the content, the information architecture, the management process and the main services provided in these environments. Characterized methodologically as an exploratory and descriptive research, with a qualitative-quantitative approach, the study was developed in two stages: the first consisted of a literature review, carried out in books, articles and academic papers dealing with the main research theme (periodical portals) to raise portal characteristics; the second involved the identification and analysis of the portals, through documentary research. Initially, there was search at the website of the Ministry of Education (in order to identify the universities in the State of Minas Gerais), followed by a verification of the university's website (to identify the existence of portals) and, finally, the analysis of each portal identified. The portal site analysis was based on content aspects (number of journals, QUALIS evaluation and area of knowledge); on the informational architecture (textual links, image links and content organization in tabs); management (institutional affiliation, portal platform, stated policies, portal history and scope, and management team); and services provided (contact information, discussion forums, search engines, and training). From the results, the existence of periodical portals in five universities was identified: Federal University of Minas Gerais, Federal University of Ouro Preto, Federal University of Juiz de Fora, Federal University of São João Del Rei and Federal University of Triângulo Mineiro. Of these institutions, only the portals at the Federal Universities of Minas Gerais and Ouro Preto meet all the elements identified in the literature regarding management, while only the first one has all the services analyzed. The results obtained showed the unevenness among the portals, the lack of specific policies in most of them, the preference for the Open Journal Systems software, the lack of sophistication of the informational architecture of the simply as directories of journals. The data analyzed lead to conclusions about the importance and contribution of information policies to subsidize the management of portals, as well as recommendations for carrying out usage studies, especially with in these environments.